PREVENTIONIS THE BESTMEDICINE: PHYSICAL EXERCISEONFHTOF CHAPADÃO DO CÉU-GO. (Fiep Bulletin - online, 2013)
As we follow the history of mankind, we shall see how notice able was the evolution of human beings both within physical, social and cultural development, however, these achievements also brought aggravating towards decreased physical endurance man light years. Technological developments brought humanity great comfort, comfort that this led to a sedentary lifestyle, risk factor and many aggravating  diseases. Knowing that the human body was designed to move, and that its performance becomes better with certain load of exercise, it is necessary to allow such physical activities and provide the population in order to remedy, ensure and promote health quality. The Department of Health Chapadão do Céu thinking in general welfare of the population in February of 2011deployedits services in health care, various forms of exercises guided by a professional Physical Education. O purpose of implementation of this program is to allow anyone to have access to exercise-oriented, choosing the mode that best fits to achieve more positive. Do part of the activities people with psychogenic disorders, special groups such as the elderly, pregnant women and hypertensive people with overweight or underweight and finally also those seeking a healthier lifestyle, thinking in maintaining overall health.
Keywords: Evolution; exercise; health